2014
DOI: 10.1016/j.optom.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fiber layer thickness in glaucomatous Nepalese eyes and its relation with visual field sensitivity

Abstract: The RNFL thickness measurements with SD-OCT are lower in glaucomatous eyes as compared to age-matched GS and normal eyes in the Nepalese population. A high resolution SD-OCT could aid significantly in the early diagnosis of glaucoma in Nepal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“…cSLO instruments, such as the Heidelberg Retina Tomography III (HRT III; Heidelberg Engineering, Heidelberg, Germany) instrument, incorporate a point laser light source which scans the retina and a confocal pinhole aperture that acts to minimise scattered and reflected light outside the image focal-plane dramatically increasing lateral resolution (10 µm) versus fundus photography and enabling retinal topographic imaging. cSLO has proven to be a useful and versatile tool for the assessment of geographic atrophy [158], epiretinal membrane characteristics [149], drusen deposits [159], fluorescein/indocyanine green angiography [89], RPE [28], retinal nerve fibre layer thickness, and optic nerve head morphology [95]. Despite the wide-range of applications for which cSLO imaging is used, this technique has several well-documented limitations, including impaired imaging in the presence of lens and corneal opacities, small pupils, and limited axial resolution (300 µm) [42].…”
Section: Techniques For Monitoring Retinal Ganglion Cell Healthmentioning
confidence: 99%
“…cSLO instruments, such as the Heidelberg Retina Tomography III (HRT III; Heidelberg Engineering, Heidelberg, Germany) instrument, incorporate a point laser light source which scans the retina and a confocal pinhole aperture that acts to minimise scattered and reflected light outside the image focal-plane dramatically increasing lateral resolution (10 µm) versus fundus photography and enabling retinal topographic imaging. cSLO has proven to be a useful and versatile tool for the assessment of geographic atrophy [158], epiretinal membrane characteristics [149], drusen deposits [159], fluorescein/indocyanine green angiography [89], RPE [28], retinal nerve fibre layer thickness, and optic nerve head morphology [95]. Despite the wide-range of applications for which cSLO imaging is used, this technique has several well-documented limitations, including impaired imaging in the presence of lens and corneal opacities, small pupils, and limited axial resolution (300 µm) [42].…”
Section: Techniques For Monitoring Retinal Ganglion Cell Healthmentioning
confidence: 99%
“…Furthermore, although a decrease in RNFL and macular thicknesses has been reported in glaucomatous eyes, there is a paucity of data on the discriminating capability of these parameters between NTG and POAG. We have previously established normative data on RNFL thickness in our population and also highlighted the relation between RNFL thickness and visual field sensitivity along with the significant potential of intraeye macular thickness asymmetry for the discrimination of NTG and POAG . In this study, we aimed to establish the distinction in these parameters between NTG and POAG to provide a new dimension to the diagnosis and management of these entities.…”
mentioning
confidence: 97%
“…Optical coherence tomography, first described by Huang and colleagues, is a new technique for real‐time, quantitative, objective, high‐resolution measurements and cross‐section imaging of the retina, from which the RNFL and macular parameters are calculated. Studies have consistently shown that both peripapillary RNFL (pRNFL) and macular thickness are lower in glaucomatous eyes . Macular thickness evaluation has received increasing attention after Zeimer and colleagues hypothesized that quantitative detection of glaucomatous damage at the posterior pole by retinal thickness mapping may provide a method for detecting and monitoring early glaucomatous damage.…”
mentioning
confidence: 99%
See 2 more Smart Citations